2019
DOI: 10.5194/acp-19-7487-2019
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting stable water isotope signals from convective and large-scale precipitation phases of a heavy precipitation event in southern Italy during HyMeX IOP 13: a modelling perspective

Abstract: Abstract. The dynamical context and moisture transport pathways embedded in large-scale flow and associated with a heavy precipitation event (HPE) in southern Italy (SI) are investigated with the help of stable water isotopes (SWIs) based on a purely numerical framework. The event occurred during the Intensive Observation Period (IOP) 13 of the field campaign of the Hydrological Cycle in the Mediterranean Experiment (HyMeX) on 15 and 16 October 2012, and SI experienced intense rainfall of 62.4 mm over 27 h wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…range. The effective reflectivity along with the Doppler velocity and the spectral range is derived from the raw Doppler spectra using the algorithm of Maahn and Kollias (2012). In order to estimate the snowfall rate, we use the reflectivity-snowfallrate (Z-S) relationship derived by Grazioli et al (2017) based on the measurements at Dumont d'Urville station.…”
Section: Measurement Datamentioning
confidence: 99%
See 1 more Smart Citation
“…range. The effective reflectivity along with the Doppler velocity and the spectral range is derived from the raw Doppler spectra using the algorithm of Maahn and Kollias (2012). In order to estimate the snowfall rate, we use the reflectivity-snowfallrate (Z-S) relationship derived by Grazioli et al (2017) based on the measurements at Dumont d'Urville station.…”
Section: Measurement Datamentioning
confidence: 99%
“…Lagrangian studies based on COSMO iso simulations have shown that δ 2 H and d in near-surface water vapour are strongly influenced by ocean evaporation and, over land, by evapotranspiration and mixing with moist air, while liquid-and mixedphase cloud formation contributes to the δ 2 H and d variability (Aemisegger et al, 2015;Dütsch et al, 2018). The importance of different air mass origins and pathways of airstreams for the SWI evolution during frontal passages has been illustrated using a COSMO iso simulation in the Mediterranean Sea (Lee et al, 2019). Idealised COSMO iso simulations of an extratropical cyclone showed that the meridional advection of air in the cold and warm sector strongly shapes the characteristic high δ values in the warm and low δ values in the cold sector (Dütsch et al, 2016, see also Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A dynamical phenomenon with a particularly strong impact on the vertical extent of shallow cumulus clouds are so-called dry air tongues (Mapes and Zuidema, 1996) or dry intrusions (Browning, 1993;Raveh-Rubin, 2017). These dry intrusions have been shown to originate from the midlatitudes (Yoneyama and Parsons, 1999) using soundings and global atmospheric analysis datasets from the Coupled Ocean-Atmosphere Response Experiment of the Tropical Ocean and Global Atmosphere programme (TOGA COARE; Webster and Lukas, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These additional water cycles are affected by the same physical processes as the light water molecule, except for isotopic fractionation during phase change processes. COSMO iso has been previously used to study various aspects of the regional atmospheric water cycle over Europe and the USA (Pfahl et al, 2012;Aemisegger et al, 2015;Dütsch et al, 2018;Christner et al, 2018;Lee et al, 2019). Here, nine COSMO iso simulations were conducted in the Southern Ocean covering the ACE measurement time period.…”
Section: Cosmo Iso Simulationsmentioning
confidence: 99%
“…Lagrangian studies based on COSMO iso simulations have shown that δ 2 H and d in near-surface water vapour are strongly influenced by ocean evaporation and, over land, by evapotranspiration and mixing with moist air, while liquid and mixed phase cloud formation contributes to the δ 2 H-and d-variability (Aemisegger et al, 2015;Dütsch et al, 2018). The importance of different air mass origins and pathways of airstreams for the SWI evolution during frontal passages has been illustrated using a COSMO iso simulation in the Mediterranean Sea (Lee et al, 2019). Idealised COSMO iso simulations of an extratropical cyclone showed that the meridional advection of air in the cold and warm sector strongly shape the characteristic high δ values in the warm and low δ values in the cold sector (Dütsch et al, 2016, see also Fig.…”
Section: Introductionmentioning
confidence: 99%